Early-stage Favourable Anal Cancer: A Retrospective Analysis of Clinical Outcomes of a Moderately Low Dose Elective Nodal Intensity-modulated Radiotherapy Schedule. Issue 7 (July 2017) - Lestrade, L.; Zilli, T.; Kountouri, M.; Jumeau, R.; Matzinger, O.; Bourhis, J.; Miralbell, R.; Ozsahin, M.; De Bari, B.
Abstract: In this retrospective study we evaluated the long-term results of 35 early-stage favourable T1-2 N0 M0 anal cancer patients treated with intensity-modulated radiotherapy techniques combining low dose prophylactic inguinal-pelvic irradiation with dose-escalated boost. Optimal locoregional control and good tolerance makes this treatment a valuable alternative to brachytherapy boost and involved-field radiotherapy plans. Highlights: We evaluated 35 early-stage favourable T1-2 N0 M0 anal cancer patients. Treatment consisted of low dose inguinal-pelvic intensity-modulated radiotherapy with a dose-escalated boost. Optimal locoregional control and good tolerance were observed. This treatment may be an alternative to brachytherapy boost and involved-field radiotherapy.